Tathbiiq Namudzaj At- Ta’allum Al-Qaaim ‘ala Al-Masyru’ fii Tathwiiri Mahaarati Al-Kitabah: Applying The Project-Based Learning Model To Develop Public Speaking Skills - hatta sabri; M.Fadli; Nasruddin (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in developing students’ speaking skills in the Arabic Language Education Program at Langsa State Islamic University. The study employs a qualitative approach with a case study method, involving lecturers and students as data sources through interviews, observations, and documentation. The results indicate that PjBL effectively enhances students’ ability to prepare and deliver Arabic speeches confidently and competently. Students actively engage in planning, executing, and evaluating speech projects, thereby simultaneously developing their language proficiency, critical thinking, creativity, and interpersonal skills. PjBL provides an authentic and contextual learning experience, integrating theory and practice harmoniously. The primary challenge observed is students’ anxiety in public speaking, which can be mitigated through guidance and self-reflection. This study underscores the importance of employing student-centered learning models to achieve superior communication competencies.